2019
DOI: 10.3892/ol.2019.10467
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison between three‑ and four‑dimensional computerised tomography radiotherapy for breast cancer

Abstract: At present, methods of radiotherapy simulation for breast cancer based on four-dimensional computerised tomography (4D-CT) or three-dimensional CT (3D-CT) simulation remain controversial. In the present study, 7 patients with residual breast tissue received whole breast radiotherapy based on 3D-CT and 4D-CT simulation. For the 4D-CT plan, four types of CT images were produced, including images of the end of inspiration and the end of expiration, and images acquired by the maximal intensity projection (MIP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…As an alternative to FB-IMRT, 3D-DIBH offers patients with left-sided breast cancer a clinically equal course of treatment while protecting vulnerable organs and being more easily implemented. In our study, the dosimetry of some organs at risk in the 4D IMRT plans was significantly lower than the 3D conformal with DIBH plans, including the mean heart dose, which is in concordance with Yanli Yan's study [26]. Regarding 4D IMRT, our findings are contrast those found in Reardon and Hayden's study, in which the mean LAD dose showed no significant difference between both the 3D conformal with the DIBH plan and the 4D IMRT plan in relation to the DIBH arm in comparison with the FB arm, and the maximum LAD dose showed no significant difference between the 3D DIBH and 4D-CT IMRT plans [22,28].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As an alternative to FB-IMRT, 3D-DIBH offers patients with left-sided breast cancer a clinically equal course of treatment while protecting vulnerable organs and being more easily implemented. In our study, the dosimetry of some organs at risk in the 4D IMRT plans was significantly lower than the 3D conformal with DIBH plans, including the mean heart dose, which is in concordance with Yanli Yan's study [26]. Regarding 4D IMRT, our findings are contrast those found in Reardon and Hayden's study, in which the mean LAD dose showed no significant difference between both the 3D conformal with the DIBH plan and the 4D IMRT plan in relation to the DIBH arm in comparison with the FB arm, and the maximum LAD dose showed no significant difference between the 3D DIBH and 4D-CT IMRT plans [22,28].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding 4D IMRT, our findings are contrast those found in Reardon and Hayden's study, in which the mean LAD dose showed no significant difference between both the 3D conformal with the DIBH plan and the 4D IMRT plan in relation to the DIBH arm in comparison with the FB arm, and the maximum LAD dose showed no significant difference between the 3D DIBH and 4D-CT IMRT plans [22,28]. With regard to V3 of the contralateral breast, it was significantly lower in the 3D conformal with the DIBH plan than in the 4D IMRT plan, which contrasts Yanli Yan et al's study [26] and supports the findings of Reardon and Hayden's study [28]. Moreover, the cervical esophagus was significantly higher in the 4D IMRT plan than in the 3D conformal plan, especially in patients with supraclavicular irradiation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In comparison with the traditional non gating 3DCT simulation, the gating method could significantly reduce the irradiation dose to normal lung tissue. IGTV retro and PTV retro , based on retrospective respiratory gating technology, provided more tumor movement information than IGTV pro and PTV pro , whereas Plan retro did not increase the irradiation dose on normal lung tissue significantly 24 …”
Section: Discussionmentioning
confidence: 93%
“…Many improvements to RT protocols have been added, such as enhanced localization and gated techniques. Three- and four-dimensional planning models and those based on positron emission tomography/X-ray computed tomography are widely implemented in practice [ 135 , 138 ]. For patients with left-sided breast cancer, intensity-modulated RT and deep inspiration breath-hold (DIBH) technique are also used to reduce the harmful effect of radiation [ 139 , 140 , 141 , 142 ].…”
Section: Radiotherapymentioning
confidence: 99%